Effects of physical distancing by COVID-19 pandemic on diet quality, neurological and immunological markers, and fecal microbiota of Brazilian older women - Longo, Priscila Larcher; de Aquino, Rita de Cassia; Ortiz, Sandra Regina Mota; de Oliveira, Roque Santos; Gavioli, Aline; do Amaral, Jônatas Bussador; Monteiro, Fernanda Rodrigues; de Almeida Franco, Raquel Riyuzo; Mereu, Giovana Rebonatti; Bachi, André Luis Lacerda; de Lima, Alexandre José Bancher; Laurentino, Gilberto Candido; et al. (Frontiers in Nutrition, 2022)
Physical distancing was used to prevent transmission of COVID- 19, however there are concerns that this may promote harmful impacts on health, such as reduced levels of physical practice and changes in food intake and gut microbiota composition. This study evaluated the impacts of six months physical distancing on Brazilian older women upon body mass index (BMI), strength, physical activity level (IPAQ), eating habits, neurological markers (brain-derived neurotrophic factor-BDNF and cortisol), cytokines (IL-2, IL-5, IL-6, IL-10, interferon-IFN-γ, tumor necrosis factor-TNF-α), aging-associated markers (vascular endothelial growth factor-VEGF, insulin-like growth factor-IGF-1, klotho and thymic stromal lymphopoietin-TSLP), besides specific groups of fecal microbiota. Fifteen women, over 60 years old, residents of São Paulo state (Brazil), were evaluated in March and in September 2020. The older adult women, with a mean age 66±6.2 years presented significantly increased BMI and high effect size for non-protective foods consumption, reduced light physical activity and strength six months following the physical distancing. Furthermore, the serum concentration of IFN-γ, IGF-1 and IFN-γ/IL-5 were significantly higher, while lower concentration of IL-2 and IL-5 were observed six months after the physical distancing. Significant increase was noted only to Blautia spp. abundance after six months of physical distancing. Several correlations were observed at both before and after physical distancing, however, interestingly, many of them were lost or inverted six months following, while new ones emerged. Taken together, these results showed that lifestyle changes and stress conditions addressed by physical distancing from the COVID-19 pandemic impacted the health of older women included in the present study. Therefore, future follow-up studies are essential to propose interventions in order to restore the health conditions observed before the pandemic period, and thus to maintain the quality of life of older adults in different socioeconomic contexts.